An Overlooked Aspect of Internationalization: Power Blocs and the “Cultural Other” in the Classroom - Ahmad Samarji (Educational Considerations, 2019)
As teachers, instructors, and educators, we strive to prepare our students to become global citizens and equip them with a degree of intercultural competence, where they can survive within a global economy and an interconnected world. However, we are sometimes too focused on the broader global picture and often overlook an essential component towards internationalization and globalization: the power blocs that exist inside our classroom. This article serves as a commentary to prompt teachers at schools, instructors at universities, and educators to ensure that a major component of our teaching and learning practice should be focused on blurring the boundaries between students of different/competing power blocs inside the classrooms. Blurring such boundaries is an essential milestone towards promoting tolerance, acceptance, and acknowledgment of the “cultural other” in today's interconnected world.
Keywords: Power Blocs; Classroom; Globalization; Internationalization; Global Citizenship; Cultural Other